Contradições e precariedades no trabalho terceirizado: o papel da gestão pública federal no enfrentamento aos dilemas da terceirização em uma instituição de ensino superior pública - Becker, Marcelo Roberto (2021)
Globalization and the advance of the capitalist system are reflected in scenarios of constant political, economic and social changes, resulting in big transformations in the world of work in recent decades. Within this panorama, it is necessary to seek answers to one of the main emerging issues: the Outsourcing of services, specifically, in Public Administration. In this way, the present study aimed to analyze how the work relationships of outsourced professionals at the Federal University of Santa Maria (UFSM) are constituted, in order to promote actions to improve the reality faced in the work at the University. This research is qualitative, exploratory, and for that the method used was the semi-structured interview. For data analysis, discourse analysis was used, based on the methodology proposed by Gagnetem (1987). The study was applied to a sample of 11 outsourced employees, 3 managers from UFSM, and 2 managers from the outsourced company, through individual interviews. The main results point to Outsourcing at UFSM as a factor of precariousness of work for outsourced workers, through: advances in outsourcing; low pay; insecurity and work overload; union weakening; discrimination and invisibility; precarious relationship between outsourced worker and service provider company; and the lack of security in the face of the COVID-19 pandemic. In addition, the study pointed to the trend of human reification in outsourced work, resulting in high turnover of the segment and lack of creation of bonds at work. Finally, the study showed that all respondents, despite the degrading situation imposed by outsourcing, recognize the importance of the work performed by the outsourced segment in the institution. Based on the results found, this study proposed improvements in order to intervene in the researched reality, among which the approximation between the UFSM Ombudsman departament and the outsourced workers at the institution stands out, in order to create a safe and welcoming space for this segment, helping to deal with the problems found.